FLASH CARDS SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB: DAMPAKNYA TERHADAP KEMAMPUAN MENULIS SISWA - Agustianda, Monica; Wasilah; Qoim Nurani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing skills (maharah al-kitābah) are an essential component of Arabic language learning; however, at the elementary school level, students’ writing proficiency remains relatively low. Many students struggle with writing Arabic letters, forming words into sentences, and using vocabulary accurately. This issue is compounded by the use of conventional teaching methods with limited visual media, resulting in low learning motivation. Based on these problems, this study aims to determine the effect of using flash cards on the Arabic writing skills of fifth-grade students at SD Muhammadiyah 18 Palembang. This research employed a quantitative approach with an experimental design involving 20 students from class V B selected through purposive sampling. The instruments used were pre-tests, post-tests, and questionnaires. Data were analyzed using normality tests, validity and reliability tests, paired sample t-tests, and N-Gain Score calculations. The results indicate that flash cards significantly improve students’ writing skills. The average pre-test score of 65.5 increased to 78.7 after the treatment. The paired sample t-test yielded a Sig. value of 0.000 < 0.05, indicating a significant difference between students’ scores before and after the use of the media. Additionally, the average N-Gain Score of 0.7393 (73.93%) falls within the high category, showing that the improvement occurred effectively. These findings demonstrate that flash cards not only enhance students’ Arabic writing skills but also create a more engaging and interactive learning environment, helping students understand vocabulary through visual support.